2022
DOI: 10.3389/fpls.2022.921700
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the High Stigma Exsertion Rate Trait in Rice by Pyramiding Multiple QTLs

Abstract: Asian cultivated rice is a self-pollinating crop, which has already lost some traits of natural outcrossing in the process of domestication. However, male sterility lines (MSLs) need to have a strong outcrossing ability to produce hybrid seeds by outcrossing with restorer lines of male parents in hybrid rice seed production. Stigma exsertion rate (SER) is a trait related to outcrossing ability. Reconstruction of the high-SER trait is essential in the MSL breeding of rice. In previous studies, we detected eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…The stigma exsertion of weedy rice, promoting the likelihood of outcrossing in nature between weedy and cultivated rice in the same area (Figure 4), created high t values (Tables 2 and 3). The rice genotype exhibiting this trait, together with male sterile ability, represents a breeding goal for the hybrid rice production system (Bakti and Tanaka 2019; Tan et al 2021, 2022; Zou et al 2020). The genetic diversity revealed in this study is higher than that previously reported by Prathepha (2011) ( H E = 0.598) and Cao et al (2006) ( H E = 0.313).…”
Section: Resultsmentioning
confidence: 99%
“…The stigma exsertion of weedy rice, promoting the likelihood of outcrossing in nature between weedy and cultivated rice in the same area (Figure 4), created high t values (Tables 2 and 3). The rice genotype exhibiting this trait, together with male sterile ability, represents a breeding goal for the hybrid rice production system (Bakti and Tanaka 2019; Tan et al 2021, 2022; Zou et al 2020). The genetic diversity revealed in this study is higher than that previously reported by Prathepha (2011) ( H E = 0.598) and Cao et al (2006) ( H E = 0.313).…”
Section: Resultsmentioning
confidence: 99%
“…The phenotypic analysis showed that the increase of SER did not lead to the change of grain shape in most pyramiding lines. The results indicated that the high-SER trait can be reconstructed by pyramiding of the QTLs in rice ( Tan et al., 2022b ). In this study, we found that grain shape is another factor affecting rice SER, which affects SER by partially affecting stigma shape ( Figures 6 and 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seven SSSLs, W17-46-40-10-07-05, W23-07-06-05-02-02, W12-11-22-03-03-163, W02-08-08-08-01, W07-07-02-03-02, W23-19-06-07-19-03 and W09-38-60-07-18-04 carrying respectively fgr , qBLAST-11 , gs3 , gs3 , gw5 , GW7 and gw8 were selected from the HJX74-SSSL library ( Wang et al., 2012 ; Zhang, 2021 ). The pyramiding lines carrying 2-4 QTLs for SER, 2QL-1, 2QL-5, 3QL-3, 3QL-10, 4QL-1 and 4QL-3, were previously constructed by pyramiding QTLs for SER from HJX74-SSSLs through maker assisted selection (MAS) ( Tan et al., 2022b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, multiple QTLs were pyramided in an attempt to rebuild the high stigma exsertion rate (SER) in rice. The study found 18 QTLs linked to SER, and the outcomes demonstrated that rice could successfully improve the SER trait by pyramiding several QTLs [ 100 ].…”
Section: Breeding Techniques For Producing Hybrid Ricementioning
confidence: 99%